Patient Experience from an eHealth Perspective: A Scoping Review of Approaches and Recent Trends - Viitanen, Johanna; Valkonen, Paula; Savolainen, Kaisa; Karisalmi, Nina; Hölsä, Sini; Kujala, Sari (Yearbook of Medical Informatics, 2022)
Objectives: Patients’ experiences are increasingly gaining interest in multiple research fields. Researchers have applied various approaches to studying patient experience (PX); however, there is no commonly agreed-upon definition of PX. This scoping review focuses on PX from an eHealth perspective. Our aim was to: 1) describe how PX has been defined, 2) investigate which factors influencing PX and components of PX have been identified and researched, 3) explore the methods used in studying PX, and 4) find out the recent trends in PX research from an eHealth perspective.Methods: We selected six major journals covering the fields of health informatics, PX, and nursing informatics. Using the search terms “patient experience” and technology-related terms (e.g., digital, eHealth), we searched for articles published between 2019 and 2021. From 426 articles, 44 were included in the analysis.Results: Multiple concepts and meanings are used to refer to PX. Few articles include vague descriptions of the concept. Numerous eHealth factors are influencing PX, as well as components considering PX. The influencing factors were related to eHealth solutions’ type and quality, and care process, when the components of PX were related to communication, remote interaction, risks and concerns, and patients’ attitudes towards telehealth. Surveys were the main method used to study PX, followed by interviews.Conclusions: PX is a complex and multifaceted phenomenon, and it is described as a synonym for patient satisfaction and telehealth experiences. Further multidisciplinary research is needed to understand PX as a phenomenon and to outline a framework for the research.
Keywords: Review; patient experience; eHealth; digital health services; electronic health services